Lack of association of ABCB1 haplotypes on five loci with response to treatment in epilepsy - Haerian, B.S.; Lim, K.S.; Mohamed, E.H.M.; Tan, H.J.; Tan, C.T.; Raymond, A.A.; Wong, C.P.; Wong, S.W.; Mohamed, Z. (2011)
Approximately one third of newly treated epilepsy patients do not respond to antiepileptic drugs (AEDs). Overexpression of P-glycoprotein (P-gp) efflux transporter has been proposed to have a critical role in causing resistance to AEDs. P-gp is a product of the ATP-binding cassette subfamily B member 1 (ABCB1) gene. The purpose of this study was to investigate a possible link between ABCB1 rs3789243 C > T, Cl 2361, G2677T/A, rs6949448 C > T, and C3435T haplotypes with response to carbamazepine (CBZ) or sodium valproate (VPA) monotherapy in Malaysian epilepsy patients. No ABCB1 haplotype association was found with response to either CBZ or VPA monotherapy in the Chinese, Indian, and Malay patients. C3435 allele carriers of the Indian males with cryptogenic epilepsy were more prone to resistance to either CBZ or VPA than carriers of T allele. Moreover, rs37892431 allele carriers of Malay females with symptomatic epilepsy were more resistant to either CBZ or VPA than C allele carriers. Our findings suggest that the ABCB1 rs3789243 C > T, C1236T, G2677T/A, rs6949448 C > T, and C3435T haplotypes do not contribute to response to AED treatment in epilepsy. (C) 2011 British Epilepsy Association. Published by Elsevier Ltd. All rights reserved.